Formulation and evaluation of orally disintegrating tablet of ondansetron using natural superdisintegrant - Shahtalebi Mohammad Ali; Tabbakhian Majid; Koosha Sina (Shahrekord University of Medical Sciences, 2015)
Introduction: Difficulty in swallowing is common among all age groups, especially elderly and pediatrics. Orally disintegrating tablets may constitute an innovative dosage form that overcome the problem of swallowing and provide a quick onset of action. This study was aimed to formulate and evaluate an orally disintegrating tablet (ODT) containing ondansetron while using semi-synthetic and natural superdisintegrants. Methods: Orodispersible tablets were prepared by direct compression using natural superdisintegrant (Karaya gum) and semi-synthetic superdisintegrant (croscarmellose). The prepared tablets were evaluated for hardness, friability, thickness, drug content uniformity, water absorption and wetting time. A 32 factorial design was used to investigate the effect of independent variables (amount of croscarmellose and Karaya gum) on dependent variables (disintegration time, friability and Q5 [cumulative amount of drug release after 5 minutes]). A counter plot was also presented to graphically represent the effect of independent variable on the disintegration time, friability and Q5. The check point batch was also prepared to prove the validity of the evolved mathematical model. The systematic formulation approach helped in understanding the effect of formulation processing variable. Results: According to the results of optimized batches, the best concentrations of superdisintegrant were as follows: 7.88 mg Karaya gum and 7.78 mg croscarmellose gave rapid disintegration in 31 seconds which showed 99% drug release within 5 minutes. Conclusion: Karaya gum, a natural superdisintegrant, gives a rapid disintegration and high release when used with synthetic superdisintegrant in formulation of ODT.